Emosi Siswa Tunanetra dalam Perencanaan Karir di Sekolah Luar Biasa (SLB) A, Payakumbuh - Lusi Yandrika; Darimis; Fadhillah Syafwar; Rosa Dovita (PT PUSTAKA CENDEKIA GROUP, 2024)
The main problem in this research is the emotions of blind students in career planning at SLB A Payakumbuh. There are still many blind students who are doubtful, anxious and confused about career planning after graduating from school. The aim of the research is to determine the emotions of blind students in career planning, the efforts of blind students in overcoming emotional problems in planning career decisions and the strategies of guidance and counseling teachers in helping them. The research method used is descriptive qualitative research. The results of this research explain that the types of emotions of blind students in career planning after graduating from school are predominantly positive emotions, such as joy and happiness, blind students' efforts to overcome emotional problems are being optimistic about future career planning, as well as carrying out activities that have a positive influence on their careers. while the guidance and counseling teacher's strategy for helping blind students is to provide individual counseling services and classical services to blind students.